DIPG-30. DIFFERENTIAL HYPOXIC RESPONSE IN HUMAN DIPG CELL LINES - Waker, Christopher (Neuro Oncol, 2017)
BACKGROUND: Diffuse Intrinsic Pontine Glioma (DIPG) are rare and aggressive childhood tumors, with an abysmal prognosis and limited experimental models available for study. A recent report showed that DIPG are hypoperfused compared to surrounding brain tissue, suggesting that the tumor cells are exposed to a hypoxic microenvironment. This stimulus may induce widespread transcriptional changes through activation of Hypoxia-inducible Factors (HIF), which have been associated with invasion, metastasis, angiogenesis, and resistance to radiation therapy and chemotherapy. Therefore, in vitro models using DIPG cells cultured in conditions of normal oxygen tension may not be representative of in vivo tumors because of artificial differences in HIF activation. METHODS: To test cellular responses to hypoxia, human DIPG cell lines with H3.1 K27M and H3.3 K27M mutations were treated with the hypoxia-mimetic compound, cobalt (II) chloride, for 24 hours. Simulated hypoxic responses were assayed using Western blot analysis, proliferation assays, and extracellular flux analysis. RESULTS: The H3.3 K27M cell line increased expression of HIF1a with cobalt (II) chloride treatment and correlated with an increase in glycolytic rates and increased expression of proteins involved in glucose transport and glycolysis. The H3.1 K27M cell line increased expression of HIF2a and not HIF1a after cobalt (II) chloride treatment, correlating with an increase in some glycolysis-associated proteins but no change in glycolytic rate. CONCLUSION: These data suggest that the effects of a hypoxic microenvironment should be considered in experimental models using cultured DIPG cell lines to understand differences in cell behavior, patient prognosis, and predicted treatment responses. Activation of specific HIF isoforms may underlie differences in hypoxic responses among cell lines.